Investigating the effect of energy dissipation on flotation kinetics in an oscillating grid flotation cell - Massey, Wesley Thomas (Department of Chemical Engineering, 2016)
This thesis investigates the effect of energy dissipation on the flotation kinetics of quartz in an oscillating grid flotation cell. Oscillating grids exhibit relatively isotropic and homogeneous turbulence, which cannot be achieved in standard impeller agitated flotation cells. Due to this they provide a potentially ideal environment in which to investigate the effects of energy dissipation on flotation kinetics. Previous work in an oscillating grid flotation cell was limited to energy dissipations of up to 0.6 kW/m³, which is low when compared to 0.6 - 3 kW/m³ commonly used in both flotation literature and industry. The current work uses a new oscillating grid cell which can operate at energy dissipations of up to 5 kW/m³. Quartz (sub 100 μm) has been floated in the new cell at energy dissipations ranging from 0.5 - 5 kW/m³ and using three discrete bubble sizes (0.13 mm, 0.24 mm and 0.82 mm). Characterisation experiments show that the new cell operates in a similar manner to the oscillating grid cell used by Changunda et al. (2008), and produces repeatable results. The effect of changing bubble and particle size on flotation kinetics is in agreement with literature findings, indicating that as a flotation device the oscillating grid cell is operating as expected.